Creating symbolic cultures of consumption: an analysis of the content of sports wagering advertisements in Australia - Deans, E.; Thomas, S.; Daube, Mike; Derevensky, J.; Gordon, J. (BioMed Central Ltd, 2016)
Background: Since 2008, Australia has seen the rapid emergence of marketing for online and mobile sports wagering. Previous research from other areas of public health, such as tobacco and alcohol, has identified the range of appeal strategies these industries used to align their products with culturally valued symbols. However, there is very limited research that has investigated the tactics the sports wagering industry uses within marketing to influence the consumption of its products and services. Method: This study consisted of a mixed method interpretive content analysis of 85 sports wagering advertisements from 11 Australian and multinational wagering companies. Advertisements were identified via internet searches and industry websites. A coding framework was applied to investigate the extent and nature of symbolic appeal strategies within advertisements. Results: Ten major appeal strategies emerged from this analysis. These included sports fan rituals and behaviours; mateship; gender stereotypes; winning; social status; adventure, thrill and risk; happiness; sexualised imagery; power and control; and patriotism. Symbols relating to sports fan rituals and behaviours, and mateship, were the most common strategies used within the advertisements. Discussion/Conclusions: This research suggests that the appeal strategies used by the sports wagering industry are similar to those strategies adopted by other unhealthy commodity industries. With respect to gambling, analysis revealed that strategies are clearly targeted to young male sports fans. Researchers and public health practitioners should seek to better understand the impact of marketing on the normalisation of sports wagering for this audience segment, and implement strategies to prevent gambling harm.